2002
DOI: 10.1080/165019702760390356
|View full text |Cite
|
Sign up to set email alerts
|

Trunk control test as a functional predictor in stroke patients

Abstract: The purpose of this study was to evaluate prospectively the Trunk Control Test (TCT) correlation at admission to rehabilitation with length of stay, functional independence measure (FIM), gait velocity, walking distance and balance measured at discharge in 28 hemiparetic patients. FIM and TCT were registered on admission. Outcome measures at discharge were: FIM, gait velocity, walking distance and balance assessed with the Berg Balance Scale and computerized posturography. TCT was significantly correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(103 citation statements)
references
References 17 publications
5
91
0
6
Order By: Relevance
“…Through the above results, increased muscle activities in rotation muscles in normal and hemiplegic groups during head rotation helped to stabilize participants' trunks. This result was similar to those of a study by Duarte 20 that reported unstable trunk control in stroke patients, as well as a study result by Roby-Brami et al 21 claiming that inefficient postural movements were caused by the limited range of motion of joints, as well as loss of appropriate coordination in trunk.…”
Section: Discussionsupporting
confidence: 81%
“…Through the above results, increased muscle activities in rotation muscles in normal and hemiplegic groups during head rotation helped to stabilize participants' trunks. This result was similar to those of a study by Duarte 20 that reported unstable trunk control in stroke patients, as well as a study result by Roby-Brami et al 21 claiming that inefficient postural movements were caused by the limited range of motion of joints, as well as loss of appropriate coordination in trunk.…”
Section: Discussionsupporting
confidence: 81%
“…[1][2][3] A variety of functional scales measuring balance are commonly used with people with stroke; however, only a few are specifically designed for this use. 4 Benaim et al 4 developed a new scale, the Postural Assessment Scale for Stroke patients (PASS), that directly addressed the need for an assessment tool that specifically measures balance in people with stroke.…”
mentioning
confidence: 99%
“…Sin embargo, a pesar de las pruebas convincentes de que el rendimiento del tronco es un importante predictor del resultado funcional después del ACV, las investigaciones que evalúan los resultados de la rehabilitación específica de este segmento son limitadas [12][13][14].…”
Section: Introductionunclassified